2020
DOI: 10.1002/mgg3.1509
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA deletion and duplication in Kearns–Sayre Syndrome (KSS) with initial presentation as Pearson Marrow‐Pancreas Syndrome (PMPS): Two case reports in Barranquilla, Colombia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
5
1
Order By: Relevance
“…Another study suggested that as low amounts as 1 ng of DNA sample should be used for MLPA reaction to get higher sensitivity (Mayorga et al, 2016). Although several authors reported successfully identified deletions (Liu et al, 2021) and duplications (Sabella‐Jiménez et al, 2020) using MLPA method, in our case, the results of the test were negative using different DNA dilutions. Conversely, long‐range PCR method detected heteroplasmic deletion using two different pairs of PCR primers.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Another study suggested that as low amounts as 1 ng of DNA sample should be used for MLPA reaction to get higher sensitivity (Mayorga et al, 2016). Although several authors reported successfully identified deletions (Liu et al, 2021) and duplications (Sabella‐Jiménez et al, 2020) using MLPA method, in our case, the results of the test were negative using different DNA dilutions. Conversely, long‐range PCR method detected heteroplasmic deletion using two different pairs of PCR primers.…”
Section: Discussioncontrasting
confidence: 65%
“…Single large‐scale deletions of mtDNA are usually identified in the blood DNA samples for the patients with Kearns‐Sayre syndrome. Deletions vary in size and location on the mitochondrial genome in different individuals, although the most reported deletion (NC_012920.1:m.8470_13446del4977), is identified in more than a third of patients with KSS and involves 4977 bp and 12 mitochondrial genes (Sabella‐Jiménez et al, 2020; Shemesh & Margolin, 2018). The molecular investigation revealed novel de novo 5888 bp mtDNA deletion (NC_012920.1:m.6069_11956del) for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…48,53 While many patients with PMPS do not survive infancy due to multisystem derangements, those who do survive with hematological management and supportive care transition to a Kearns-Sayre syndrome (KSS) diagnosis in childhood or adolescence. 48,52,[54][55][56][57] Improvement in bone marrow, pancreatic, hepatic, and renal parameters over time in PMPS may be explained by the frequent division of cells in these organs, allowing for selection against cells with mitochondrial DNA deletions, while the transition to a more predominantly myopathic phenotype reflects the post-mitotic state of skeletal muscle and accumulation of mitochondrial DNA deletions in myocytes over time. 52…”
Section: Pearson Marrow-pancreas Syndromementioning
confidence: 99%
“…In autopsy specimens, parathyroid glands are atrophic or even absent ( 96 ). Yet, in more recent reports, hypomagnesemia, which is commonly associated with hypoparathyroidism from suppression and/or impaired function of parathyroid hormone, has been described in few case reports ( 97 , 98 ).…”
Section: Clinical Features Of Mitochondrial Disease—endocrinementioning
confidence: 99%